China in 2020 a new type of superpower - Hu, Angang (The Thornton Center Chinese thinkers series, 2011)
"Explains how China, as the world's largest emerging market, will impact global economic growth, FDI flows, energy consumption, climate change, and other arenas, with a proposed strategic framework that would guide the country's rise while maximizing positive impacts and minimizing any negative externalities"--Provided by publisher.